The Influence of Animated Video Media on Dietary Pattern Knowledge in Grade VI School-Age Children - Khafiatun Busroh; Armenia Diahsari; Istinengtiyas Tirta Suminar (Institut Citra Internasional, 2026)
Nutritional knowledge refers to the ability to select food as a source of nutrients and to make appropriate eating choices. A child's positive attitude on health may not directly influence their behavior positively; yet, a negative attitude on health definitely affects their behavior adversely. One aspect is the knowledge of dietary patterns. Currently, some children continue to struggle with selecting healthy and nutritious food for their bodies. Consequently, health education through animated videos is necessary to enhance children's understanding of healthy dietary patterns. This study aims to determine the effect of animated video media on the knowledge of dietary patterns among sixth-grade students at SD (State Elementary School) Sonosewu, Bantul, Yogyakarta. This study employed a quantitative research methodology, specifically utilizing a Pre-Experimental Design characterized by a One Group Pre-Test - Post-Test framework. The sample comprised of 47 respondents selected by the Total Sampling Technique. The research utilized a knowledge questionnaire as its instrument. The analysis employed the Wilcoxon Signed Ranks Test for statistical evaluation. The results indicated that the Wilcoxon Signed Ranks Test obtained a value of 0.000 (p < 0.05), indicating an effect of animated video media on the awareness of dietary patterns among elementary school children. The utilization of animated video media significantly impacts the dietary patterns of sixth-grade students at SD Sonosewu, Bantul, Yogyakarta. Students are expected to anticipate dietary patterns and learn to mitigate the negative effects of insufficient knowledge regarding these dietary patterns before and after meals.